Understanding risk factors for musculoskeletal disorders in Iranian housewives: Development of a comprehensive health promotion behavior model - Samaneh Norouzi; Sedigheh Sadat Tavafian; Rosanna Cousins; Hamidreza Mokarami (BMC, 2023)
Abstract Background Chronic musculoskeletal problems are a major source of disability, reduced productivity and poor quality of life. Prevalence of musculoskeletal disorders among Iranian housewives is particularly high. Understanding how housework causes the injuries, mobility restrictions and pain associated with musculoskeletal disorders is vital to developing health promotion behavior models to support intervention. The aim of this qualitative study was to explore the experiences of housewives with musculoskeletal disorders and, according to the risk factors identified, to develop a comprehensive behavior change framework to facilitate implementing a musculoskeletal health-promoting training intervention for women. Methods Twenty-four in-depth interviews were conducted with Iranian housewives aged 20-65 years experiencing musculoskeletal pain over a 13-month period from September 2020 to October 2021. The conventional content analysis approach was used to interrogate the data. The transcript of each interview was considered a unit of analysis, and data analysis was performed using MAXQDA2018 software. Results The analysis of the interview data provided 1432 meaning units. From these codes, a conceptual framework was developed. This comprehensive model is comprised of 24 subcategories, eight categories and three themes: Individual and social predictors of MSDs and their control, Risk factors for MSDs, and Prevention and treatment of MSDs. Altogether the developed conceptual framework specified the multiple risk factors for MSDs in housewives. The findings were aligned to various health promotion models, and it was seen that ecological models, especially the Theory of Triadic Influence, can be very helpful as a supportive roadmap to implementing multilateral interventions to improve the quality of life of housewives. Conclusions This study developed an evidence based comprehensive model that identifies the individual, psychosocial, and cultural factors that influence the status of MSDs in women's domestic work to support the development and implementation of effective ergonomic interventions to manage potentials for MSDs.